Pertimbangan Hakim dalam Memutus Perkara Tindak Pidana Kekerasan Dalam Rumah Tangga (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to find out and understand the judge's considerations, which is one aspect that is crucial in determining the realization of the value of a judge's decision that gives a sense of justice (ex aequo et bono). From legal considerations that are considered prismatically, it will produce values ​​of legal certainty, justice, and benefits simultaneously. This research is a normative legal research conducted by examining laws and regulations, books, and journals related to the writing theme. Based on the results of the research, it was concluded that the criminal responsibility of perpetrators of domestic violence based on court decisions consists of 2 components, namely juridical considerations, namely judgments made by judges based on judicial facts that were revealed at trials determined by law and required to be included in decisions and non-juridical considerations based on legal provisions and a sense of social justice. As for implementing restorative justice in domestic violence cases, it is applied as a consideration to protect family coherence, especially in fortifying children's futures. Humans think the best way to help victims of crime is to catch the criminals. By paying attention to the Law on the Elimination of Domestic Violence and the Criminal Procedure Code, the results of court decisions relating to crimes of domestic violence consider the concept of punishment based on restorative justice which is oriented towards recovery efforts and the interests of the perpetrator and the victim of the crime carried out through 5 methods, namely the sufferer culprit mediation, own family organization conferencing, restorative conferencing, community restorative forums, and restorative circles or restorative